Triphalangeal thumb with delta phalanx in a case of Klinefelter's syndrome. - Lai, M M (1991)
We report a case of Klinefelter's syndrome owing to maternal meiotic error associated with triphalangeal thumb and delta phalanx bilaterally. There are no previous reports of similar cases and triphalangism with delta phalanx abnormalities of both thumbs might therefore be considered a further, but rare, manifestation of this aneuploidy.